2019
DOI: 10.1158/1078-0432.ccr-18-1254
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Angiogenesis in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) accounts for about 90% of all primary liver cancers and is the second leading cause of cancer-related deaths worldwide. The hypervascular nature of most HCC tumors underlines the importance of angiogenesis in the pathobiology of these tumors. Several angiogenic pathways have been identified as being dysregulated in HCC, suggesting they may be involved in the development and pathogenesis of HCC. These data provide practical targets for systemic treatments such as those targeting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
315
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(328 citation statements)
references
References 105 publications
6
315
0
7
Order By: Relevance
“…Until recently, sorafenib, an oral, systemic, multikinase inhibitor, was the only approved treatment for advanced HCC and demonstrated a modest improvement in survival with an increased incidence of adverse events when compared with placebo . While several phase 3 studies of targeted therapies failed to show improvement over sorafenib in the first‐line setting, a few targeted therapies have recently been approved in different settings including lenvatinib in the first‐line setting, and regorafenib and cabozantinib following progression on first‐line therapy . Recent exploratory analyses suggest median overall survival (OS) of up to 26 months may be achieved with sequential treatments, but will require prospective studies to confirm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, sorafenib, an oral, systemic, multikinase inhibitor, was the only approved treatment for advanced HCC and demonstrated a modest improvement in survival with an increased incidence of adverse events when compared with placebo . While several phase 3 studies of targeted therapies failed to show improvement over sorafenib in the first‐line setting, a few targeted therapies have recently been approved in different settings including lenvatinib in the first‐line setting, and regorafenib and cabozantinib following progression on first‐line therapy . Recent exploratory analyses suggest median overall survival (OS) of up to 26 months may be achieved with sequential treatments, but will require prospective studies to confirm.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have initially been promising clinical results with immune checkpoint inhibitors, their role in this disease remains uncertain. Despite these advances, the current prognosis for advanced disease remains dismal with median OS ranging from 7.3 to 13.6 months, median progression‐free survival (PFS) from 3.1 to 7.4 months and objective response rates from 2% to 24% …”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the sixth most common malignancy worldwide and ranks the fourth cause of lethal tumor (Bray et al, 2018). HCC is a typical hypervascular tumor and commonly associated with hypervascularity (Srivastava et al, 2018;Morse et al, 2019). Therefore, inhibiting angiogenesis is believed to be a potential strategy to control HCC (Taketomi, 2016;Barbhuiya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular adenocarcinoma (HCC) is regarded as one of the most life-threatening cancers around the world [29][30][31]. Recently, it was reported that overexpression of VEGFR-2 in HCC promotes pathological angiogenesis [32,33]. Hence, the application of VEGFR-2 inhibitors in HCC is considered one of the most successful approaches to hinder the growth and spread of hepatic cancer cells [33][34][35].…”
mentioning
confidence: 99%